Reliability Analysis of Benchmark Water Distribution System - Nair, Suja S; Meyyappan, P L (Communications - Scientific Letters of the University of Zilina, 2024)
Water is a necessary component of urban structures and a source of life. Nowadays water distribution system's performance might decline for various reasons, resulting in water waste, hence, to maintain a reliable water distribution network, assessing each water distribution study's validity is crucial. Therefore, this research has focused on using durability assessment to evaluate a water supply system. A water distribution network includes an overhead tank and nodes, pipelines, and nodes. The hydraulic properties of every node as well as pipe, including pressure and flow, are calculated utilizing EPANET. This research evaluates the reliability analysis based on the benchmark data's various diameter of pipes, such as 0.6 m, 0.4 m, 0.3 m, 0.2 m, and 0.15 m, usage. Finally, this research analyses the reliability of each set of diameter pipes in the water supply system.
Keywords: water distribution system; reliability analysis; water supply; network design; environmental protection agency network evaluation tool (EPANET)